Personal Agency Scale in higher education: design and measurement: personal agency scale - Maytorena Noriega, María de los Angeles (Consorcio de Universidades Mexicanas A.C., 2020)
The concept of human agency was been used since ancient times with a philosophical perspective and gradually got up to other social disciplines. The research present in the specialized literature shows varied and different ways of measuring it, always through other constructs. Given this conceptual diversity of the agency, the purpose of the study was to build a scale of personal agency for the educational field based on the proposal of Bandura, theoretically made up of four elements: intentionality, foresight, self-reactivity and self-reflection. Participants were 254 students of Physical Culture and Sports (n = 85), Engineering (n = 62) and Psychology (n = 107) chosen by an intentional non-probabilistic sampling of a public university in northwestern Mexico, of which 53.9% were women. The students of the sample stand out both in intentionality (intentions regarding their academic plans and the strategies to carry them out) and in self-reactivity (building ways of acting and motivating and regulating their learning-oriented execution). The tetrafactorial model of personal agency resulting from confirmatory factor analysis (AFC) presents adequate values ​​of goodness of practical adjustment. The relevance of the construction and validity of this scale has both methodological and practical implications, when addressing the need to homogenize the operationalization of the personal agency and the four elements that constitute it, for university students used in the diagnosis and promotion of the personal agency.